Comparação dos efeitos da ventilação mecânica não invasiva contínua e intermitente sobre parâmetros cardiorrespiratórios e modulação autonômica de indivíduos saudáveis - Pacagnelli, Francis L.; Freire, Ana Paula C. F. [UNESP]; Palma, Mariana R. [UNESP]; Paes, Laio L.; Cardoso, Murylo V.; Vanderlei, Luiz Carlos M. [UNESP] (My University, 2016)
Study design: Cross-sectional study. Objective: To evaluate the influence of continuous and intermittent noninvasive mechanical ventilation (NIV) on cardiac autonomic modulation and cardiorespiratory parameters in healthy women. Methods: Twenty subjects performed two types of NIV: continuous through CPAP and intermittent through Müller Reanimator. Initially they remained at rest for 20 minutes in spontaneous breathing. Then volunteers were subjected to 20 minutes of NIV application with the selected technique and finally remained at rest for 20 minutes in spontaneous breathing. Cardiorespiratory parameters and heart rate variability (HRV) were measured in all these moments. Results: There were no significant differences when comparing the two techniques. Differences were observed in HRV and cardiorespiratory parameters when analyzed individually. Lower values of heart rate and respiratory rate were observed in continuous ventilation when compared to values during ventilation with spontaneous breathing (p <0.005). In both techniques we observed significant increases in SpO2 during ventilation compared to spontaneous breathing. We observed an increase in parasympathetic modulation (RMSSD, HF ms2 and SD1) and overall variability (SDNN, RR triangular and SD2) in both techniques when compared ventilation to spontaneous breathing (p <0.005). Conclusion: There was no difference comparing the two types of NIV. However, when analyzed individually we observe different behavior of cardiorespiratory parameters and autonomic modulation.
Comparison of the effects of continuous and intermittent non invasive mechanical ventilation on cardiorespiratory parameters and autonomic modulation of healthy individuals
Keywords: Autonomic Nervous System; Healthy Volunteers; Heart Rate; Noninvasive Ventilation; Respiratory Rate; Ventilation